A robust, freeze-resistant and highly ion conductive ionogel electrolyte towards lithium metal batteries workable at −30 °C. Issue 11 (15th March 2021) - Tang, Jiaqi; Zhai, Binbin; Liu, Jianfei; Ren, Wenhao; Han, Yu; Yang, Hui; Chen, Yongsheng; Zhao, Chuan; Fang, Yu
Abstract : The wide applications of lithium metal batteries have encountered a severe conductivity issue when operating in cold weather. Abstract : The wide applications of lithium metal batteries have encountered a severe conductivity issue when operating in cold weather. Here we report a freeze-resistant lithium metal battery, which displays outstanding rate performance, negligible polarization deterioration, and a good capacity retention of 94.25% after 700-cycles of use at −30 °C, the lowest temperature ever reported for gel electrolyte-based lithium metal batteries. Remarkably, the lithium metal batteries are even workable at temperatures down to −60 °C. The key point of the innovative design is the utilization of a newly created anti-freezing ionogel as an electrolyte, which is produced by gelation of an electrochemically inert ionic liquid, 1-butyl-3-methylimidazolium tetrafluoro-borate ([BMIM]BF4 ), via dynamic condensation of a specially designed benzaldehyde-terminated polyethylene glycol (PEG-CHOs) with the tetra-hydrazide derivative of p-tert -butyl-calix[4]arene (CTH). The as-prepared ionogel electrolyte demonstrates a high ionic conductivity (0.43 mS cm −1 ), a broad stability window (2.4–4.3 V vs. Li + /Li), and high flexibility at −30 °C. The outstanding property of the ionogel electrolyte is ascribed to its unique gel network structure as it enables enrichment of Li + and enhances its efficient transportation. Further tests demonstrate that the ionogel electrolyte could be also used for the assembly of flexible lithium metal batteries.